UMP Eid Fitr Celebration - Munira, Abdul Razak (Pusat Bahasa Moden dan Sains Kemanusiaan, 2012)
13 September 2012. UMP’s annual Eid Fitr celebration was held in front of the Chancellery building. Apart from celebrating the coming of Syawal, the event aimed at strengthening ties among UMP’s community, staff and students alike.